Determination of cation exchange capacity and analysis of cation availability in hemic and sapric peat with different preparation and extraction methods - Mirna Anriani Siregar; Azwar Ma'as; Makruf Nurudin (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
The use of mineral soil analysis procedures in peat soils is considered unsuitable. Peat soil is vulnerable to disturbance, which leads to the damage of peat inert structure, such as the sifting and drying process. The objective of this study was to obtain the proper methods of preparation and extraction to be used in peat soils that can reflect the conditions on field. The experiment was carried out in the laboratory of Soil Science Department UGM by using the peat soil samples taken from Padang Island, Riau, arranged in a factorial randomized block design with three factors (peat soil preparation, the extraction method, and the level of peat maturity). The variables observed included the available cation and Cation Exchange Capacity (CEC) of the peat soil. The results showed that there was no significant effect of the treatment interactions on each variable observed. The preparation method for original soil at each level of peat maturity reflected more of the physical condition on the field more than other methods. Meanwhile, sapric peat showed significant effect on cations and CEC. After being converted to bulk density (BD) values at each level of peat maturity, the result of the leaching extraction method showed that the value of available cation and CEC that reflected more of the value on the field. The peat soil analysis method should be carried out without air drying and shaking extraction treatment for further research.